Paediatric Health Professionals as Parent Educators: A Developing Role? - Reeder, Jim; Morris, Jane (International Journal of Practice-based Learning in Health and Social Care, 2016)
The purpose of this study was to develop an improved understanding of the perception of health professionals regarding the provision of information to parents of children with long-term disabilities. The aim was to generate new perspectives, inform debate, and to identify practical suggestions for health professionals. This study adopted a qualitative approach, guided by a phenomenological methodology. Seven health professionals, working within an Integrated Children and Young Person’s Therapy Service of a single UK National Health Service (NHS) foundation trust, participated in semi-structured, in-depth interviews. The resultant data were analysed using a rigorous, systematic process of thematic content analysis. Two main themes were identified and discussed. Theme 1 was ‘parent readiness for information’; with subthemes 1A ‘assessing parent readiness’ and 1B ‘developing parent readiness’. Theme 2 was ‘role as information manager’. (It is acknowledged that a further theme ‘relationship with parents’ was identified; which will be presented and discussed in another article). The following conclusions were drawn. The health professional’s role, as a provider of information to parents of children with disabilities, is evolving and may now be more helpfully described as that of a parent educator. It is suggested that this may involve a shift in focus from content/timing of information provision to the development of parents as learners. It is also suggested that it would be useful for health professionals to explore opportunities for practice-based initiatives to support the development of the skills required for this role.